Olfactory impairment in monozygotic twins discordant for schizophrenia - Ugur, Tarik Naci Norbert; Weisbrod, Matthias; Franzek, E.; Pfüller, Ute; Sauer, H. (European archives of psychiatry and clinical neuroscience, 2005)
Several studies demonstrated olfactorydysfunction in patients with schizophrenia,some reported deficient olfaction in unaffected relativesof schizophrenics as well. This study differentially assessedolfactory acuity as well as smell identificationand smell discrimination in monozygotic twins discordantfor schizophrenia and healthy, monozygotic controltwins, to determine the genetic basis of differentolfactory modalities and their association to schizophrenia.
Published online: 12 November 2004
Gesehen am 26.01.2021